ニチ イ コクサイ キョウドウ カンソク ホウコク イタリア キチ ニ オケル リクジョウ セイブツ カンソク ト セツエイ - 伊村, 智; イムラ, サトシ; Imura, Satoshi (1999)
P(論文) イタリアとの外国共同観測「南極域における生物地理学的多様性の研究」の初年度として, テラノバベイ基地において1998年12月4日より1999年1月15日まで, 陸上植生観測を行った。基地周辺の植物・土壌動物をサンプリングし, 特に蘚苔類植生について昭和基地周辺との生物地理学的な多様性の比較を試みた。同時に, テラノバベイ基地の設営面の特徴を調査した。 From December 4,1998 to January 15,1999,the author stayed at Baia Terra Nova Station (Italy) in Antarctica, as an exchange scientist. To compare the biodiversity between Syowa Station and the Baia Terra Nova Station area, many samples of mosses, lichens, algae and micro animals in the soil were collected, and the structure of moss vegetation was studied in various fields around the station. Some characteristic features of logistics at the station were also researched. departmental bulletin paper